Pollen morphology and numerical analysis of Tamarix L. (Tamaricaceae) in Egypt and its systematic implication (Bangladesh Journal of Plant Taxonomy, 2017)
A palynological and multivariate study of six species of Tamarix L. distributed in Egypt was carried out. Pollen morphology was examined by Light Microscope (LM) and Scanning Electron Microscope (SEM). The systematic study of these species was conducted by means of numerical analysis using UPGMA clustering and PCO analysis based on 33 morphological characters, including life form, vegetative parts, fruits, floral characters, seeds and pollen grains. Pollen grains were found to be monads, radially symmetrical, isopolar, small-sized and homocolpate. Tamarix nilotica can be easily separated from other taxa by its subprolate pollen shape. Two major clades were identified by multivariate analysis of morphological characters; one of them included three species, namely T. amplexicaulis, T. passerinoides and T. macrocarpa. Our results indicate that there is a wide range of morphological similarity among the species of section Polyadenia. The other clade included T. aphylla, T. tetragyna and T. nilotica from section Tamarix and section Oligadenia.Keywords: Tamarix; Pollen Morphology; Numerical Taxonomy; UPGMA Cluster; PCO, Egypt.Bangladesh J. Plant Taxon. 24(1): 91105, 2017 (June)